Basic Principles of Landscape Design - Gail Hansen (EDIS)
Revised! Circular 536, a 12-page illustrated circular by Gail Hansen, explains the design process that landscape designers use, that systematically considers all aspects of the land, the environment, the growing plants, and the needs of the user to ensure a visually pleasing, functional, and ecologically healthy design. Published by the UF Department of Environmental Horticulture, July 2010.